Penerapan Metode Holt-Winter Exponential Smoothing Dalam Prediksi Jumlah Siswa-Siswi Baru Di Sma Negeri 09 Bengkulu Selatan - Wiwin Irianto Saputra; Indra Kanedi; Dimas Aulia Trianggana (UNIVED Press, 2024)
Admission of new students is a routine activity carried out every academic year at the school. High School 09 South Bengkulu is one of the high schools in South Bengkulu Regency which accepts new students every academic year. The number of new students is based on the gender of the new students (boys and girls) and age group (14-15 years, 16-17 years, and 18-19 years). The application of the Holt-Winter Exponential Smoothing Method in predicting the number of new students at South Bengkulu High School 09 can make it easier to obtain information on predictions of the number of students in the school in the upcoming new academic year, where the prediction of the number of new students is based on gender. New students (boys and girls) and age groups (14-15 years, 16-17 years, and 18-19 years). Based on data obtained from South Bengkulu High School 09, the predicted results for the number of students were obtained. female students for the 2024/2025 academic year, namely 65 male students in the 14-15 year age group, 42 female students in the 14-15 year age group, 42 female students, 16-17 year old male students as many as 31 students, female gender in the 16-17 year age group as many as 0 students, male gender in the 18-19 year age group as many as 3 students, and female gender in the 18-19 year age group as many as 0 Students.